The changing epidemiology of the ageing thalassaemia populations: A position statement of the Thalassaemia International Federation. (15th April 2020) - Farmakis, Dimitrios; Giakoumis, Anastasios; Angastiniotis, Michael; Eleftheriou, Androulla
Abstract: Therapeutic advances in β‐thalassaemia have gradually lead to a significant improvement in prognosis over the past few decades. As a result, patients living in areas where disease‐specific programmes offering access to modern therapy are in place experience a new era of prolonged survival that tends to reach that of the normal population. This ageing thalassaemia population, however, faces a new spectrum of comorbidities resulting from increasing age that may jeopardise the advances in prognosis provided by current therapy and thus poses new challenges in diagnosis, monitoring and treatment. In this position paper of the Thalassaemia International Federation, we review the changing epidemiology and clinical spectrum of patients with β‐thalassaemia and propose actions to be undertaken in order to address the emerging spectrum of comorbidities resulting from ageing.